Prolog / Programming for Artificial Intelligence - Bratko Ivan (Addison-Wesley Publishing Company, 2001)
This book concentrates on the art of using the basic mechanisms of Prolog to solve interesting problems. Foreword, Preface, The Prolog Language, Introduction to Prolog, Syntax and Meaning of Prolog Programs, Lists and Operators and Arithmetic, Using Structures: Example Programs, Controlling Backtracking, Input and Output, More Built-in Predicates, Programming Style and Technique, Operations on Data Structures, Advanced Tree Representations, Prolog in Artificial Intelligence, Basic Problem-Solving Strategies, Best-First Heuristic Search, Problem Decomposition and AND/ OR Graphs, An Expert System Shell, Planning, Machine Learning, Qualitative Reasoning, Game Playing, Meta-Programming, Index.